PATTERNS OF OXIDATIVE ASSIMILATION IN STRAINS OF ACETOBACTER AND AZOTOBACTER - Tomlinson, Geraldine A. (1963)
Tomlinson, Geraldine A. (The University of British Columbia, Vancouver, B.C., Canada), and J. J. R. Campbell. Patterns of oxidative assimilation in strains of Acetobacter and Azotobacter. J. Bacteriol. 86:1165–1172. 1963.—Oxidative assimilation of glucose-U-C(14) was studied with washed-cell suspensions of Acetobacter aceti, A. xylinum, Azotobacter vinelandii, and A. agilis. The suggestion that oxidative assimilation is largely the incorporation of endogenously produced ammonia is tenable. A. aceti did not exhibit oxidative assimilation and it did not incorporate ammonia in the presence of glucose, α-ketoglutarate, or pyruvate. A. xylinum, A. vinelandii, and A. agilis incorporated C(14) into the nitrogenous fractions of the cell. The level of assimilation into A. xylinum was low due to the accumulation of extracellular cellulose, and the level of assimilation into the Azotobacter was low presumably because of the requirement of energy for nitrogen fixation. The Azotobacter were characterized by the presence of a high level of radioactivity in the cold trichloroacetic acid-soluble pool. None of the organisms accumulated compounds in the supernatant fluid that might be considered pacemakers in glucose oxidation, and this could be a contributing factor in the low level of assimilation.